Analyzing Self-Perception Theory in Lady Gaga’s "Born This Way": A Psychological Study of Identity and Social Freedom - Nurcahyani, Nabila Putri; Leonard, Les Vis; Rynoldy, Efron Trivosa; Anggraeni, Dewi (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
Pop music has long been recognized as a potent vehicle for cultural expression, yet its specific function as a cognitive behavioral tool remains under-explored in literary and psychological studies. While musical anthems are often viewed primarily as entertainment, recent interdisciplinary research suggests they play a crucial role in shaping individual identity and facilitating psychological resilience. Addressing this intersection of pop culture and social psychology, this study analyzes Lady Gaga’s anthem, "Born This Way," through the lens of Daryl Bem’s (1967) Self-Perception Theory. The primary objective is to investigate how the song functions not merely as an artistic expression of solidarity, but as a specific psychological instrument for identity reconstruction. Methodologically, the research utilizes a qualitative textual analysis to systematically map specific lyrical directives against Bem’s theoretical framework, interpreting them as behavioral stimuli that precede attitude formation. By examining cues such as the physical command to "put your paws up," the grooming ritual of "rolling hair," and the role-adoption of "being a queen," the analysis identifies how these external actions influence the listener’s self-concept. The results indicate that the song’s repetitive verbal affirmations and the rejection of "drag" (insecure) behaviors effectively reprogram the listener’s self-image by validating a "behavior-first" approach to confidence. Furthermore, the article connects these lyrical interventions to developmental psychology, illustrating how external validation and active social posturing foster a sense of social freedom. Ultimately, this research concludes that "Born This Way" operates as a mechanism for self-liberation, proving that the performance of confident actions is a precursor to the internal realization of self-worth